Poverty Convergence in a Time of Stagnation : A Municipal-Level Perspective from Mexico (1992-2014) - Lopez-Calva, Luis F.; Ortiz-Juarez, Eduardo; Rodriguez-Castelan, Carlos (World Bank, Washington, DC, 2019)
This paper exploits a novel municipal-level data set to explore patterns of convergence in income and poverty in Mexico during 1992-2014. The paper finds that, despite a context of overall stagnant economic growth and poverty reduction, there is evidence of income and poverty convergence at the municipal level. The findings suggest that these convergence processes stem from a combination of considerable positive performance among the poorest municipalities and stagnant and deteriorating performance among richer municipalities. Re distributive programs, such as federal transfers to poor municipalities and cash transfers to poor households, seem to have played an important role in driving these results by bolstering income growth among the poorest municipalities, while also inducing progressive changes in the distribution of income.